Pengaruh Kualitas Produk, Selera Konsumen, Citra Merek, Cita Rasa, Dan Harga Terhadap Keputusan Pembelian Pada Rajo Seblak Siteba Melalui Selera Konsumen Dan Cita Rasa Sebagai Variabel Intervening - Bahri, Aulia Febriyanti; Jolianis, Jolianis; Ramayani, Citra (CERED Indonesia Institute, 2024)
This research aims to analyze (1) the effect of product quality on consumer tastes, (2) the effect of brand image on cunsumer tastes, (3) the effect of price on customer tastes, (4) the effect of product quality on savor, (5) the effect of consumer tastes on savor, (6) the effect of brand image on savor, (7) the effect of price on savor, (8) the effect of product quality on purchasing decisions, (9) the effect of consumer tastes on purchasing decisions, (10) the effect of brand image on purchasing decisions, (11) the effect of savor on purchasing decisions, (12) the effect of price on purchasing decisions. The time of this research is in July 2024. This type of research is descriptive and associative research. The population in this study is consumers who make purchases at Rajo Seblak Siteba. The sample amounted to 120 people with a sampling technique in the form of purposive sampling. The research instrument used in this study is a closed questionnaire (questionnaire) with path analysis testing. The data analysis techniques used are descriptive analysis techniques and inductive analysis techniques, with the help of the Eviews 10 and SPSS version 18 programs.